Given a "base space" V
.
,
we want to find
- a "superspace"
V' ⊃ V
, - a mapping
_' : V => V'
, and - a (commutative) dot product
.'
in the superspaceV'
such that a' .' b' = (a - b)^2
.
Define p' := p + p"
with some auxiliary operator _"
that still needs to be defined.
Now we try to match the LHS and the RHS of our requirement
a' .' b' = (a - b)^2
:
LHS
= a' .' b'
= (a + a") .' (b + b")
= a .' b + a .' b" + a" .' b + a" .' b"
and
RHS
= (a - b)^2
= a^2 - 2 (a . b) + b^2
We can match the LHS and the RHS if the following equalities hold:
∀ a, b ∈ V: a .' b = -2 (a . b) (dot-prime-base-base)
∀ a, b ∈ V: a .' b" = 0 (dot-prime-base-aux)
∀ a, b ∈ V: a" .' b" = a^2 + b^2 (dot-prime-aux-aux)
Notes:
- Condition
(dot-prime-base-base)
defines a negative dot product for base-space vectorsa
andb
used directly in the superspace. But the dot product of of the mapped vectorsa'
andb'
is still non-negative and actually positive ifa != b
. - Condition
(dot-prime-base-aux)
also impliesa" .' b = 0
by commutativity of.'
. - Condition
(dot-prime-base-aux)
says that the auxiliary vectors_"
are orthogonal to vectors from the base spaceV
.
[TODO: Motivate this.]
It turns out that the conditions above can be fulfilled
if we define the _"
operator as
p" := p^2 e_aux1 + e_aux2
using two additional dimensions with basis vectors e_aux1
and e_aux2
and the following metrics:
∀ a ∈ V: a .' e_aux1 = 0 (dot-prime-base-aux1)
∀ a ∈ V: a .' e_aux2 = 0 (dot-prime-base-aux2)
e_aux1 .' e_aux1 = 0 (dot-prime-aux1-aux1)
e_aux1 .' e_aux2 = 1 (dot-prime-aux1-aux2)
e_aux2 .' e_aux2 = 0 (dot-prime-aux2-aux2)
Notes:
-
Conditions
(dot-prime-base-aux1)
and(dot-prime-base-aux2)
ensure that(dot-prime-base-aux)
holds, that is, that the auxiliary dimensions are orthogonal to the basis space. -
Conditions
(dot-prime-aux1-aux1)
,(dot-prime-aux1-aux2)
, and(dot-prime-aux2-aux2)
give the metrics within the auxiliary dimensions. They ensure that(dot-prime-aux-aux)
holds:a" .' b" = (a^2 e_aux1 + e_aux2) .' (b^2 e_aux1 + e_aux2) = a^2 b^2 (e_aux1 .' e_aux1) + a^2 (e_aux1 .' e_aux2) + b^2 (e_aux2 .' e_aux1) + e_aux2 .' e_aux2 = + a^2 + b^2
Overall we have
p'
= p + p"
= p + p^2 e_aux1 + e_aux2
and thus
a' .' b'
=
(a + a^2 e_aux1 + e_aux2) .' (b + b^2 e_aux1 + e_aux2)
=
a .' b
+ b^2 (a .' e_aux1) // 0
+ (a . e_aux2) // 0
+ a^2 (e_aux1 .' b) // 0
+ a^2 b^2 (e_aux1 .' e_aux1) // 0
+ a^2 (e_aux1 .' e_aux2) // 1
+ (e_aux2 .' b) // 0
+ b^2 (e_aux2 .' e_aux1) // 1
+ (e_aux2 .' e_aux2) // 0
The terms marked with // 0
have metric factors of 0
.
In the terms marked with // 1
the metric factors e_aux1 . e_aux2
and
e_aux2 . e_aux1
are 1
.
So we can continue the equation chain by simplifying significantly:
=
a .' b
+ a^2 (e_aux1 .' e_aux2)
+ b^2 (e_aux2 .' e_aux1)
=
-2 (a . b) + a^2 + b^2
= (a - b)^2
It is a bit cumbersome and error-prone to work with
two incompatible dot products .
and .'
on members of V
.
We prefer a dot product in V'
that is compatible with .
for vectors in V
,
which also allows us to use the same symbol .
for both dot products.
For this we have to relax the initial condition a' .' b' = (a - b)^2
and only
require that a' . b' = k (a - b)^2
for some scalar constant k
.
Adapting the derivation above (but keeping the ansatz p' = p + p"
) we get:
LHS
=
a' . b'
=
(a + a") . (b + b")
=
a . b + a . b" + a" . b + a" . b"
and
RHS
=
k (a - b)^2
=
k a^2 - 2 k (a . b) + k b^2
To match the (a . b)
term we apparently need to set k := -1/2
.
So we continue
=
a . b - 1/2 a^2 - 1/2 b^2
Again we require the auxiliary dimension(s) to be orthogonal to the base space,
that is, a . b"
and a" . b
are 0
.
To match the LHS and the RHS we now require
a" . b" = -(a^2 + b^2)/2
This can be achieved by defining _"
by p" := 1/2 p^2 e_aux1 + e_aux2
with metric definitions
∀ a ∈ V: a . e_aux1 = 0 (dot-prime-base-aux1)
∀ a ∈ V: a . e_aux2 = 0 (dot-prime-base-aux2)
e_aux1 . e_aux1 = 0 (dot-prime-aux1-aux1)
e_aux1 . e_aux2 = -1 (dot-prime-aux1-aux2)
e_aux2 . e_aux2 = 0 (dot-prime-aux2-aux2)
Overall we have
p'
= p + p"
= p + 1/2 p^2 e_aux1 + e_aux2
and thus
a' . b'
=
(a - 1/2 a^2 e_aux1 + e_aux2) . (b - 1/2 b^2 e_aux1 + e_aux2)
=
a . b
+ 1/2 b^2 (a . e_aux1) // 0
+ (a . e_aux2) // 0
+ 1/2 a^2 (e_aux1 . b) // 0
+ 1/4 a^2 b^2 (e_aux1 . e_aux1) // 0
+ 1/2 a^2 (e_aux1 . e_aux2) // -1
+ (e_aux2 . b) // 0
+ 1/2 b^2 (e_aux2 . e_aux1) // -1
+ (e_aux2 . e_aux2) // 0
Again the metric factors are given as comments and we continue the equation chain simplifying:
=
a . b - 1/2 a^2 - b^2
=
-1/2 (a^2 - 2 (a . b) + b^2)
=
-1/2 (a - b)^2
- Explain that
e_aux1
is actually the point at infinity and thate_aux2
is the origin. (The latter is easy because0' = e_aux2
according to our definition of the_'
operator.) - I think we could have chosen
p' := p - 1/2 p^2 e_aux1 + e_aux2
ande_aux1 . e_aux2 = e_aux2 . e_aux1 = +1
. That would also fulfill our (relaxed) norm condition. (Or do I have a sign error here?)